The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1037/neu0000348
|View full text |Cite
|
Sign up to set email alerts
|

A specific implicit sequence learning deficit as an underlying cause of dyslexia? Investigating the role of attention in implicit learning tasks.

Abstract: Dyslexic children do not suffer from a specific implicit sequence learning deficit. The slower RTs of the dyslexic children throughout the entire implicit sequence learning process are caused by their comorbid attention problems and overall slowness. A key finding of the present study is that, in contrast to what was assumed for a long time, implicit learning relies on attentional resources, perhaps even more than explicit learning does. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 61 publications
3
21
0
Order By: Relevance
“…In this study, we first examined how children with dyslexia performed on a sequential and a spatial implicit learning task compared to typical readers. We found no significant differences in learning rate on the sequential or spatial task in children with dyslexia and typical readers, in line with more recent literature (Schmalz, Altoè, & Mulatti, 2017;Staels & van den Broeck, 2017;Vakil et al, 2013). However, the standardized mean difference effect size of 0.33, 95% confidence interval [−0.06, 0.72], for the sequential implicit learning task, was in the same direction as in the meta-analysis by Lum et al (2013).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, we first examined how children with dyslexia performed on a sequential and a spatial implicit learning task compared to typical readers. We found no significant differences in learning rate on the sequential or spatial task in children with dyslexia and typical readers, in line with more recent literature (Schmalz, Altoè, & Mulatti, 2017;Staels & van den Broeck, 2017;Vakil et al, 2013). However, the standardized mean difference effect size of 0.33, 95% confidence interval [−0.06, 0.72], for the sequential implicit learning task, was in the same direction as in the meta-analysis by Lum et al (2013).…”
Section: Discussionsupporting
confidence: 90%
“…The authors found a mediumweighted effect size (.449) for the SRT task, but there was substantial heterogeneity between studylevel effect sizes (varying from −.710 to 1.172), and not all studies included in the meta-analysis found significant differences between participants with dyslexia and typical readers. This lack of a significant difference between participants with dyslexia and typical readers is also found in more recent implicit learning studies comparing adults (Henderson & Warmington, 2017) or children (Staels & van den Broeck, 2017;Vakil et al, 2013) with and without dyslexia.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Studying the P1 and N1 components in relation to the SRT task may provide new insights into the role of attention in implicit sequence learning. Indeed, the extent to which attentional processes are necessary for implicit learning have been an area of ongoing debate (Curran & Keele, 1993;Jiménez & Méndez, 1999;Staels & Van den Broeck, 2017).…”
Section: P1 and N1 Erp Components And Sequence Learning On The Srt mentioning
confidence: 99%
“…Evidence has shown EEG + tDCS, fMRI+ tDCS, or fNIRS + tDCS can be used to monitor tDCS-induced changes of the neural activities involved in sustained attention (Miller et al, 2015), semantic processing (D'Mello et al, 2017), and spatial working memory (McKendrick et al, 2015), all of which have also been found to be impaired in the individuals with reading difficulties (Schulz et al, 2008; Pham and Hasson, 2014; Staels and Van den Broeck, 2017). As such, those neuroimaging methods can also be integrated into future tDCS-based reading interventions to detect the potential neural changes, which can be taken as an additional outcome measure.…”
Section: Adding Outcome Measures By Using Neuroimaging Methodsmentioning
confidence: 99%